Prevalence of Helicobacter pylori vacA and cagA Genotypes in Ethiopian Dyspeptic Patients - Asrat, Daniel (American Society for Microbiology, 2004)
A total of 300 gastric biopsy samples and 50 Helicobacter pylori isolates were collected from Ethiopian adult dyspeptic patients. The vacA and cagA genes were detected in 90 and 79% of biopsy specimens, respectively, and in 100 and 87% of clinical isolates, respectively. Both genes were detected in 84% of the gastric biopsy samples and in 87% of the clinical isolates. Among vacA genotypes, the s1/m1 genotype was the most common in gastric biopsy samples (48%). The vacA and cagA positive H. pylori strains were detected to a higher degree in patients with chronic active gastritis (71%) than patients with other histopathological findings (29%) (P < 0.05).